Charlotte Brontë and Victorian psychology - Shuttleworth, Sally, 1952- (Cambridge studies in nineteenth-century literature and culture ;, 1996)
"This ground-breaking study successfully challenges the traditional tendency to regard Charlotte Bronte as having existed in a historical vacuum, by setting her work firmly within the context of Victorian psychological debate. Based on extensive local research, using texts ranging from local newspaper copy to the medical tomes in the Reverend Patrick Bronte's library, Sally Shuttleworth explores the interpenetration of economic, social and psychological discourse in the early and mid nineteenth century, and traces the ways in which Charlotte Bronte's texts operate in relation to this complex, often contradictory, discursive framework. Shuttleworth offers a detailed analysis of Bronte's fiction, informed by a new understanding of Victorian constructions of sexuality and insanity, and the operations of medical and psychological surveillance."--Jacket